Photosynthetic Pigments and Biochemical Response of Zucchini (Cucurbita pepo L.) to Plant-Derived Extracts, Microbial, and Potassium Silicate as Biostimulants Under Greenhouse Conditions - Abd-Elkader, Doaa Y.; Mohamed, Abeer A.; Feleafel, Mostafa N.; Al-Huqail, Asma A.; Salem, Mohamed Z. M.; Ali, Hayssam M.; Hassan, Hanaa S. (Frontiers in Plant Science, 2022)
There are many technological innovations in the field of agriculture to improve the sustainability of farmed products by reducing the chemicals used. Uses of biostimulants like plant extracts or microorganisms are a promising process that increases plant growth and the efficient use of available soil resources. In order to determine the effects of some biostimulants’ treatments on the photosynthesis pigments and biochemical composition of zucchini plants, two experiments were conducted in 2019 and 2020 under greenhouse conditions. In this work, the effects of beneficial microbes (Trichoderma viride and Pseudomonas fluorescens), as well as three extracts from Eucalyptus camaldulensis leaf extract (LE), Citrus sinensis LE, and Ficus benghalensis fruit extract (FE) with potassium silicate (K2SiO3) on productivity and biochemical composition of zucchini fruits were assessed as biostimulants. The results showed that E. camaldulensis LE (4000 mg/L) + K2SiO3 (500 mg/L) and T. viride (106 spore/mL) + K2SiO3 (500 mg/L) gave the highest significance yield of zucchini fruits. Furthermore, the total reading response of chlorophylls and carotenoids was significantly affected by biostimulants’ treatments. The combination of K2SiO3 with E. camaldulensis LE increased the DPPH scavenging activity and the total phenolic content of zucchini fruits, in both experiments. However, the spraying with K2SiO3 did not observe any effects on the total flavonoid content of zucchini fruits. Several phenolic compounds were identified via High-performance liquid chromatography (HPLC) from the methanol extracts of zucchini fruits like syringic acid, eugenol, caffeic acid, pyrogallol, gallic acid, ascorbic acid, ferulic acid, α-tocopherol, and ellagic acid. The main elemental content (C and O) analyzed via Energy-dispersive X-ray spectroscopy (EDX) of leaves were affected by the application of biostimulants. The success of this work could lead to the development of cheap, and easily available safe biostimulants for enhancing the productivity and biochemical of zucchini plants.